Domestic Violence Between Childhood Incest and Re-victimization: A Study Among Anti-violence Centers in Italy - Testoni, Ines; Mariani, Chiara; Zamperini, Adriano (Frontiers in Psychology, 2018)
The term incest concerns Child Sexual Abuse (CSA) where the perpetrator is a member of the family. It is a traumatic experience that causes many disorders in the life of the survivors, who are mostly women. It is a phenomenon transversal to all social classes and is often underestimated because it is still censored and not always specifically assessed in social or health services. Since these survivors are often re-victimized in intimate relationships, this study wanted to survey whether the Italian anti-violence services had considered the problem and how. About 112 centers were contacted, but only 13 participated in the research, while 16 operators were interviewed to reconstruct the biographies of 32 victims. The need to standardize the psychotherapeutic support to these re-victimized women was discussed, and a critique to the un-discriminated de-pathologization was presented. In particular, we wanted to underline that even if this approach is useful for treating victims who were not abused in infancy, it is insufficient for women who suffered from incest.